Экспериментальное исследование аккумуляторных батарей электрических торпед, находящихся на послегарантийных этапах эксплуатации - Анипко, О. Б.; Редин, Н. Н.; Щепцов, О. В. (НТУ "ХПИ", 2013)
На підставі проведених експериментальних досліджень акумуляторних батарей торпед, що знаходяться на післягарантійних етапах експлуатації, показані зміни, що відбуваються з елементами і складовими частинами акумуляторної батареї.

On the basis of the conducted experimental researches of storage batteries of torpedoes being on the after guarantee stages of exploitation, the changes what is going on with elements and component parts of storage battery are shown.
Experimental research storage batteries of electric torpedoes, being on after guarantee stages of exploitation
Keywords: противолодочная торпеда; низкие температуры; ударно-вибрационное воздействие; техническая документация; конструкторская документация